Dihydroisoxazole Analogs for Labeling and Visualization of Catalytically Active Transglutaminase 2 - Dafik, Laila (2011)
We report the synthesis and preliminary characterization of “clickable” inhibitors of human transglutaminase 2 (TG2). These inhibitors possess the 3-halo-4,5-dihydroisoxazole warhead along with bio-orthogonal groups such as azide or alkyne moieties that enable subsequent covalent modification with fluorophores. Their mechanism for inhibition of TG2 is based on halide displacement, resulting in the formation of a stable imino thioether. Inhibition assays against recombinant human TG2 revealed that some of the clickable inhibitors prepared in this study have comparable specificity as benchmark dihydroisoxazole inhibitors reported earlier. At low micromolar concentrations they completely inhibited transiently activated TG2 in a WI-38 fibroblast scratch assay, and could subsequently be used to visualize the active enzyme in situ. The potential use of these inhibitors to probe the role of TG2 in celiac sprue as well as other diseases is discussed.